2022
DOI: 10.1002/mats.202200044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Structure of Reactive Polymers on Network Structure and Mechanical Properties of Gels

Abstract: The effects of the primary structure of multifunctional reactive polymers on the network structure and the mechanical properties of gels formed by crosslinking the reactive polymers with crosslinkers are studied by a coarse‐grained molecular dynamics simulation. When functional groups are randomly arranged on the polymers, the network structure, such as the number densities of elastically effective chains and entanglements, and the mechanical properties depend on the number average molecular weight of the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Since M n,p is almost the same in all the gels, the number of dangling ends rarely varies. 43 The differences in the cross-linked structure between the gels with almost the same composition are caused by kinetic effects. 33 The increase in ν x due to the change in the synthesis method from the FRP to the CRP is attributed to the change of the network strands from the loop, which is a defect in the cross-linked structure, into the bridge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since M n,p is almost the same in all the gels, the number of dangling ends rarely varies. 43 The differences in the cross-linked structure between the gels with almost the same composition are caused by kinetic effects. 33 The increase in ν x due to the change in the synthesis method from the FRP to the CRP is attributed to the change of the network strands from the loop, which is a defect in the cross-linked structure, into the bridge.…”
Section: Resultsmentioning
confidence: 99%
“…Although the molecular weight distribution of the primary chains differs between the CRP gel and the FRP gel, we have confirmed that the difference in the molecular weight distribution does not significantly affect the network structure. 43…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation